Regulated Antisense RNA Eliminates Alpha-Toxin Virulence in Staphylococcus aureus Infection - Ji, Yinduo (American Society for Microbiology, 1999)
The ability to selectively disrupt gene function remains a critical element in elucidating information regarding gene essentiality for bacterial growth and/or pathogenesis. In this study, we adapted a tet regulatory expression system for use in Staphylococcus aureus, with the goal of downregulating gene expression via induction of antisense RNA. We demonstrate that this system exhibits a 50- to 100-fold dose-dependent level of induction in bacterial cells grown in culture (i.e., in vitro) and also functions in mice (i.e., in vivo) following oral administration of inducer. To determine whether induced antisense RNA could interfere with chromosomally derived gene expression, we cloned a fragment of the S. aureus alpha-toxin gene (hla) in antisense orientation downstream of the tet promoter system and introduced the construct into S. aureus. Induced antisense hla RNA downregulated chromosomally derived hla gene expression in vitro approximately 14-fold. Similarly, induction of hla antisense RNA in vivo dramatically reduced alpha-toxin expression in two different murine models of S. aureus infection. Most importantly, this reduction completely eliminated the lethality of the infection. These results indicate that the tet regulatory system functions efficiently in S. aureus and induced antisense RNA can effectively downregulate chromosomal gene expression both in vitro and in vivo.